Hidden politicization: labor conflicts and antagonisms during the first cycle of peasant mobilization in Curicó, Chile (1938-1947) - Alderete Soto, Pablo Francisco; Brangier Peñailillo, Víctor Mauricio (Revista de historia., 2025)
This article examines the phenomenon of informal peasant politicization in Curicó province, Chile (1938-1947), through labor lawsuits, framing judicialization as a pivotal mechanism for legitimizing socio-economic demands. Using unpublished sources from Labor Courts and agricultural statistics, it explores how peasants combined traditional forms of resistance with legal channels, creating a culture of resistance that fueled formal associativity strategies under the Popular Front government. The findings highlight the correlation between judicial conflicts, union expansion, and daily resistance to the hacienda model through the demand for agrarian rights, aimed at supporting the self-reproduction of peasant economy and culture.